URRENT SITUATION IN ASKANIA-NOVA AND BLACK SEA BIOSPHERE RESERVES - Arkhipova, Galyna; Zagrebelna, Irina (Proceedings of National Aviation University (archive), 2006)
The following information includes general date about both Askania-Nova and Black Sea biosphere reserves. It describes general climatic, ecological, geological and other conditions of reserves development. The main part is devoted to information about environmental problems of the reserves, including consideration of Black Sea environmental state. Also some political and geographical problems are represented in the presentation.